Clinical Value of Circulating Microribonucleic Acids miR-1 and miR-21 in Evaluating the Diagnosis of Acute Heart Failure in Asymptomatic Type 2 Diabetic Patients - Al-Hayali, Mutaa Abdalmutaleb; Sozer, Volkan; Durmus, Sinem; Erdenen, Fusun; Altunoglu, Esma; Gelisgen, Remise; Atukeren, Pinar; Atak, Palmet Gun; Uzun, Hafize (MDPI, 2019)
To investigate whether the circulating miR-1 (microRNA-1) and miR-21 expression might be used in the diagnosis of heart failure (HF) and silent coronary artery disease (SCAD) in asymptomatic type 2 diabetes mellitus (T2DM) patients and to explore the relationship of these miRs with N-terminal pro-brain natriuretic peptide (NT-proBNP) and galectin-3. One hundred thirty-five consecutive patients with T2DM and 45 matched control subjects were enrolled in the study. This study consisted of the following four groups: control group (mean age: 60.23 +/- 6.27 years, female/male (F/M): 23/22); diabetic group (DM) (mean age: 61.50 +/- 5.08, F/M: 23/22); DM + SCAD group (mean age: 61.61 +/- 6.02, F/M: 20/25); and DM + acute HF group (mean age: 62.07 +/- 5.26 years, F/M: 20/25). miR-1 was downregulated in the DM, CAD + DM and HF + DM groups by 0.54, 0.54, and 0.12 fold as compared with controls, respectively. The miR-1 levels were significantly lower in HF + DM than DM with 0.22 fold changes (p < 0.001); and in patients with CAD + DM group with 0.22 fold changes (p < 0.001). Similarly, miR-21 was overexpressed in patients with DM, CAD + DM, and HF + DM with 1.30, 1.79 and 2.21 fold changes as compared with controls, respectively. An interesting finding is that the miR-21 expression was significantly higher in the HF + DM group as compared with the CAD + DM group; miR-1 was negatively correlated with NT-proBNP (r = -0.891, p < 0.001) and galectin-3 (r = -0.886, p < 0.001) in the HF + DM group; and miR-21 showed a strongly positive correlation with (r = 0.734, p < 0.001) and galectin-3 (r = 0.764. p < 0.001) in the HF + DM group. These results suggest that the circulating decreased miR-1 and increased miR-21 expression are associated with NT-proBNP and galectin-3 levels in acute HF + DM. Especially the miR-21 expression might be useful in predicting the onset of acute HF in asymptomatic T2DM patients. The miR-21 expression is more valuable than the miR-1 expression in predicting cardiovascular events of acute HF and the combined analysis of miR-21 expression, galectin-3, and NT-proBNP can increase the predictive value of miR-21 expression.
Keywords: asymptomatic type 2 diabetes mellitus; acute heart failure; silent coronary artery disease; NT-proBNP; galectin-3; miRNA-1; miRNA-21; BRAIN NATRIURETIC PEPTIDE; HIGH GLUCOSE; MORTALITY; PHOSPHATASE; MICRORNAS; OUTCOMES; IMPACT; Biochemistry & Molecular Biology